2022
DOI: 10.3390/insects13010074
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Non-Lethal High-Temperature Stress on the Development and Reproductive Organs of Bradysia odoriphaga

Abstract: Bradysia odoriphaga is an agricultural pest in China’s vegetable industry. In this study, pupae and adults were exposed to various non-lethal high-temperatures. The results demonstrated a decreased rate of eclosion once the pupae were exposed to temperatures exceeding 37 °C for 1 h. No effect on the lifespan of unmated female adults was observed after exposure to temperature stress, while unmated male adult lifespan decreased (>37 °C for 2 h). The size of the testis and ovaries for unmated male and female a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Here, we found that by the age of 16 days, under normal environmental conditions, both the testes in males and ovaries in females were found to be fully mature, containing well-developed sperm and eggs, respectively. Previously researches revealed that high temperature damaged the development of reproductive organs in many insects, such as Bradysia odoriphaga, Drosophila suzukii and Agasicles hygrophila (Hu et al, 2022;Green et al, 2019;Zhao et al, 2016). In this study, we similarly found that exposing newly emerged adults of M. alternatus to heat stress for a duration of fteen days adversely affected the development of their reproductive organs.…”
Section: Discussionsupporting
confidence: 63%
“…Here, we found that by the age of 16 days, under normal environmental conditions, both the testes in males and ovaries in females were found to be fully mature, containing well-developed sperm and eggs, respectively. Previously researches revealed that high temperature damaged the development of reproductive organs in many insects, such as Bradysia odoriphaga, Drosophila suzukii and Agasicles hygrophila (Hu et al, 2022;Green et al, 2019;Zhao et al, 2016). In this study, we similarly found that exposing newly emerged adults of M. alternatus to heat stress for a duration of fteen days adversely affected the development of their reproductive organs.…”
Section: Discussionsupporting
confidence: 63%
“…The reproductive organs of certain insect species undergo gradual development and maturation during the pupal stage. Previous studies have indicated that subjecting the pupae of these insects to non-lethal high-temperature stress has a greater impact on adult reproductive traits compared to applying heat stress to adult insects (Walsh et al 2021;Hu et al 2022). All these ndings make it reasonable to hypothesize that the stage at which insect reproductive organs mature is more susceptible to high temperatures in relation to reproductive traits.…”
Section: Stage-speci C Differences In Detrimental Effects Of Ehts On ...mentioning
confidence: 99%
“…Previous studies have indicated that subjecting the pupae of these insects to nonlethal high-temperature stress had a greater impact on adult reproductive traits compared to applying heat stress to adult insects. 32,33 All of these findings made it reasonable to hypothesize that the stage at which insect reproductive organs mature was more susceptible to high temperatures about reproductive traits.…”
Section: Stage-and Sex-specific Effects Of Ehts On Reproductive Traitsmentioning
confidence: 99%